CHRONIC PAIN - Qo’ldosheva Mo’tabar Muhtarovna (TADQIQOTLAR, 2026)
Chronic pain is a long-lasting pain that persists for more than three months or continues beyond the normal healing period of an injury or illness. Unlike acute pain, which serves as a protective mechanism to alert the body to injury, chronic pain often remains even when the original cause has been resolved. It is considered one of the most common and complex health problems worldwide, affecting people of all ages and significantly impacting their quality of life.